Limitations of temporal (forehead) temperature readings as a screening method for covid-19 - Luis Fernando Aragón-Vargas (Pensar en Movimiento)
At the end of May 2020, the Covid-19 pandemic had resulted in over 6 million confirmed cases and more than 350.000 deaths worldwide (Total confirmed COVID-19 deaths, n. d.). Multiple public-health strategies have been attempted in different regions of the world as authorities try to control spread of the disease, while the SARS-CoV-2 virus responsible for the pandemic proves to be extremely contagious. As many countries attempt the return to business as usual, in what has been called “a new normality”, a key element in the prevention of contagion is reasonable screening for infected people.A common, generalized screening method involves measuring body temperature to detect fever. While fever is not specific to Covid-19, it is regarded as a method with good sensitivity for this disease (de Oliveira Neto, de Oliveira Tavares, Schuch, & Lima, 2020). Body temperature testing before admission is currently recommended in a wide variety of health care scenarios (Krengli, Ferrara, Mastroleo, Brambilla, & Ricardi, 2020; Rombolà et al., 2020; Sainati & Biffi, 2020); this type of screening is also commonly observed in TV reports before people are admitted to health care clinics, restaurants, worksites, or public transportation. Finally, screening for fever is part of the World Health Organization recommendations for management of ill travelers at international borders (World Health Organization [WHO], 2020). Apparently, the method of choice for this fever screening is to measure temporal artery (forehead) temperature with different infrared, contactless devices which provide for a practical, reasonably safe, and quick reading. However, while any effort to detect potentially ill individuals is commendable, the accuracy, reliability and validity of such readings have not been evaluated on the field. In this editorial, I intend to briefly review some basic physiology and epidemiology, together with published field studies with exercising humans, to explore some of the limitations associated with the use of field temporal temperature readings (Ttemp) as a screening method for Covid-19.